2012
DOI: 10.3736/jcim20121104
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of randomized controlled trials of integrative medicine therapy for treatment of chronic severe hepatitis

Abstract: Integrated Chinese and Western medicine can promote the recovery of liver function and coagulation function, and reduce the mortality rate of patients with chronic severe hepatitis. However, due to a lower quality of clinical trials published in Chinese journals, the evidence is insufficient to prove the superiority of integrative therapy. Further well-designed, multicenter, large-sample RCTs are still needed to evaluate the beneficial effects of CHM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…By reading the full text of the article, 1 article containing non-RCTs and 2 articles with incomplete data were excluded. Included in 15 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] SRs/Mas are journal literature, involving a total of 224 studies, including 20,710 patients, with a time span of 2013 to 2023.…”
Section: Search Results and Basic Characteristics Of The Included Stu...mentioning
confidence: 99%
See 3 more Smart Citations
“…By reading the full text of the article, 1 article containing non-RCTs and 2 articles with incomplete data were excluded. Included in 15 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] SRs/Mas are journal literature, involving a total of 224 studies, including 20,710 patients, with a time span of 2013 to 2023.…”
Section: Search Results and Basic Characteristics Of The Included Stu...mentioning
confidence: 99%
“…The ROBIS evaluation revealed that within Phase 2, in Domain 1, none of the 15 studies included provided a systematic reviews Zhang et al 2023 [30] RCT 10 716 1b, 1e, 2a, 5a, 6 TCM/TCM+WM WM Cochrane Li et al 2021 [31] RCT 5 535 1a, 2a , 4a TCM+WM WM Cochrane Liu et al 2021 [32] RCT 19 1517 1b, 2c, 2d, 2f, 3b, 3c, 3d, 3e TCM+WM WM Cochrane Mo et al 2021 [33] RCT 48 4356 1b, 3f, 6 TCM+WM WM Cochrane Liu et al 2020 [34] RCT 12 1088 1b, 1d, 4d, 3a, 5b, 6 TCM/TCM+WM WM Cochrane Ji et al 2016 [35] RCT 11 1169 1b, 2a, 1f, 6 TCM/TCM+WM WM Cochrane Sun et al 201 [36] RCT 13 1556 1b TCM WM Jadad Tian. 2019 [37] RCT 5 612 1b, 5b, 6 TCM/TCM+WM TCM/WM Jadad Zhu et al 2017 [38] RCT 19 1996 1b TCM+WM WM Jadad Dou et al 2022 [39] RCT 8 680 1b, 3f, 4a, 3d, 3e, 6 TCM+WM WM Cochrane Gao et al 2019 [40] RCT 23 1901 1a, 2c, 2d, 2h, 6 TCM+WM WM Cochrane Bai et al 2013 [41] RCT 14 1232 1b, 1c, 2h, 2c, 2e, 3f, 3h, 3j, 5b, 6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with development of medical science, complementary and alternative medicine displays its unique role in hepatitis treatment [68]. Traditional Chinese medicine (TCM), known for its holistic concept and treatment based on syndrome differentiation, emphasizes formulae employment more than single drug use in treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%